Implementation of Coaching-Based Academic Supervision in Enhancing Student Well-Being at MAS Ulumuddin, Lhokseumawe - Riza Darmayanti; Susi Yusrianti; Jumat Barus (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
The coaching approach in academic supervision offers a new paradigm that is more collaborative and constructive, in which supervisors act as partners who accompany teachers in developing their professional potential. The concept of student welfare encompasses various dimensions of student welfare, including physical, psychological, social, and academic aspects. Student welfare is important because it correlates positively with academic achievement, social adaptation, and character development. This thesis is designed to conduct research on the implementation of coaching- based academic supervision in realizing student well-being and the obstacles faced by the Madrasah Principal in implementing coaching-based academic supervision at MAS Ulumuddin. This research is qualitative research with a descriptive analysis approach. The primary data sources in this study are the Madrasah Principal, teachers, and students. Secondary data sources include academic supervision records, supervision schedules, and supporting documents. The research results are as follows: 1) The implementation of coaching-based academic supervision at MAS Ulumuddin is carried out systematically through the stages of planning, implementation, evaluation, and follow-up. This approach emphasizes partnership between the school principal and teachers in a reflective and collaborative environment, thereby enhancing teachers' professional competencies. This supervision significantly contributes to improving student well-being through responsive, participatory, and student-centered learning. 2) Challenges faced by the principal in implementing coaching-based academic supervision at MAS Ulumuddin include limited supervision time, resistance from some teachers to a reflective culture, limited understanding of the independent curriculum among teachers, and inadequate learning resources such as projectors. Despite this, the principal demonstrated commitment through follow-up actions such as training, mentoring, providing resources, and routine monitoring.